The Health System And Its Role In Crisis Management - China Case Study- - Boutora, Fadila; Louafi, Ala Eddine (جامعة الوادي - University of Eloued, 2022)
This study aims to highlight the effective role of effective health systems in crisis management under the Corona pandemic, and the study found China's digital health strategies to combat the global epidemic, provided different uses from China's digital health strategy, provided a context for how artificial intelligence and ict support health care and the needs of citizens of the world's largest country in terms of population, and also found that the success of the Chinese health system in managing the Corona pandemic crisis was primarily based on existing modern and advanced technologies. Mainly on artificial intelligence, in the end the study recommended the need to place health system programs in the priorities of planned government programs, due to their direct impact on development plans, as well as the need to adopt modern and advanced techniques based on artificial intelligence in the health sector
مقال
Keywords: Health Systems, Crisis Management, Corona Pandemic, Chinese Experience.